Design of complex profile extrusion dies through numerical modeling - Gonçalves, N. D. (2013)
The achievement of a balanced flow is one of the major tasks encompassed in the design of profile extrusion dies [1]. For this purpose numerical modeling codes may be a very useful aid. The research team involved in this work has been working during the last decade on the development of numerical tools to aid the conception of extrusion dies [1,2]. The design code developed so far carries out the automatic search of a final geometry via an optimization routine coupled with geometry and mesh generators and a 3D computational fluid dynamics (CFD) code based on the finite volume method (FVM). This CFD code is able to model the flow of polymer melts in confined channels, but is inadequate to deal with complex geometries, since it is limited to structured meshes. This work describes the recent efforts made to enlarge the scope of the design procedures, that are currently focused on the development of a modeling code able to deal with unstructured meshes. This code solves the continuity and linear momentum conservation equations, with generalized Newtonian fluids, using a SIMPLE based approach. This paper describes the developed numerical modelling code and its employment in a case study that involves the design of a medical catheter extrusion die, focused on the search of a balanced flow distribution. The results obtained show that the developed numerical code is able to deal with complex geometrical problems, being thus a valuable tool to aid the design of extrusion dies to produce complex profiles.